Persisting type 2 endoleaks following EVAR for AAA are associated with AAA expansion - Hatzl, Johannes; Wang, Vivian; Hakimi, Maani; Uhl, Christian; Rengier, Fabian; Bruckner, Thomas; Böckler, Dittmar (Journal of endovascular therapy, 2023)
Purpose:To determine the evolution of abdominal aortic aneurysm (AAA) diameter in the presence of persisting type 2 endoleaks (pEL2) following endovascular abdominal aortic aneurysm repair (EVAR). Materials and Methods:This is a retrospective, single-center, case-control study. All patients with pEL2 (pEL2 group, persisting for > 12 months) between 2004 and 2018 were identified and compared with a 1:1 age- and gender-matched control with no endoleak (control group). Primary outcome measures were freedom from AAA expansion and freedom from AAA shrinkage over time. AAA diameter measurements were performed on computed tomography angiography (CTA). Secondary outcome measures were survival, AAA-related mortality, reinterventions for pEL2, incidence of secondary type 1 endoleaks (EL1), and infrarenal aortic branch vessel anatomy.Results:A total of 773 patients were treated with EVAR for AAA between 2004 and 2018. Of them, 286 patients demonstrated type 2 endoleaks (EL2) in postoperative CTA or intraoperative angiography (37%). Forty-five of 286 EL2 (15.7%) were pEL2 (pEL2 group). Freedom from AAA expansion in the pEL2 group was 100%, 96.7%, 85.2%, and 54.3% after 1, 2, 3, and 4 years, respectively, compared with 100% after 1, 2, 3, and 4 years in the control group (p<0.01). Freedom from AAA shrinkage in the pEL2 group after 1, 2, 3, and 4 years was 95.5%, 90.4%, 90.4%, and 79.1%, respectively, compared with 86.7%, 34.8%, 19.3%, and 19.3% in the control group (p<0.01). Overall survival at 1, 2, 3, and 4 years was 100%, 97.6%, 95.0% and 95.0% in the pEL2 group and 100% at 1, 2, 3, and 4 years in the control group (p=0.17). There were no AAA-related deaths in either group. Patients with pEL2 had a significantly increased number of infrarenal aortic branches (p<0.05, respectively). Eighteen patients (40.0%) in the pEL2 group underwent 34 reinterventions for pEL2, with a median follow-up (FU) of 925 days (0?4173). Clinical success was achieved in 9 patients (50.0%). Four patients (8.9%) with pEL2 developed secondary EL1 after a median FU of 1278 days (662?2121).Conclusion:pEL2 are associated with AAA expansion during midterm FU. Further studies are warranted to evaluate the association of AAA expansion due to pEL2 with clinical outcomes to allow recommendations with regard to treatment indications.
Gesehen am 20.03.2023